IMPLEMENTATION OF COOPERATIVE LEARNING INDEX CARD MATCH ON SECONDARY STUDENTS’ SCIENCE COGNITIVE LEARNING OUTCOMES - Yulivia, Andini Dwi Yulivia; Sari, Monica Prima (JPPIPA (Jurnal Penelitian Pendidikan IPA), 2023)
Science learning is often associated with difficult topic to understand, lecture-dominated instructions, and low participation rate in classroom learning. Similar situation is observed at a secondary school in West Sumatra province, Indonesia. The observation also revealed that students’ cognitive learning outcomes is still under the minimum passing criteria for the topic of the earth’s layer. To the citizen of an area that is in high-risk of natural disaster occurrence, sound understanding on the topic is crucial. Since science lesson is designed to develop students’ thinking and problem-solving ability, such understanding is important regarding students’ survival rate. If this situation remains unaddressed, it is concerning that achieving the goals of science lesson, especially related to the topic of Earth’s layer, will be constrained. Therefore, this study offers a solution by implementing the Cooperative Learning Index Card Match (CL-ICM) to see its impact on students’ cognitive learning outcomes. This quasi-experimental research used non-equivalent control group design andh purposive sampling technique to select 67 seventh graders from two classes as experiment and control group. A set of 20 multiple-choice questions was validated and tested for reliability as research instruments to measure students’ learning outcomes. Data was then analyzed with parametric statistics technique followed by hypothesis testing using independent sample t-test. The result of data analysis gave the sig. of 0.091, which led us to decide that the null hypothesis is accepted and research hypothesis (Ha) is rejected. Therefore, it can be summarized that the implementation of CL-ICM does not give significant impact on students’ cognitive learning outcomes on the topic of the earth’s layer.